Long distance fathers the effects of Information Communication Technology (ICT) on seafarers' families in Minglanilla, Cebu - Panoril, Kareen Jean B. (2016)
Abstract: Due to their families? financial needs, which cannot be sustained by working in the Philippines, seafarer fathers leave their families to work abroad. This long distance situation has effects on the family dynamics and the fathers? roles in parenting. Particularly, communication, which has a vital role in family relationships, is mostly relied upon Information Communication Technologies (ICTs). With the increasing number of seafarer families, understanding the role and effects of ICTs in the family communication become more important. This study explores how the use of ICTs by selected families from Minglanilla, Cebu affect their perceptions and attitudes towards their seafarer father?s parenting. Respondents of this study were members of Apostleship of the Sea (AoS) ? Cebu, a Catholic ministry providing pastoral services to seafarers and their families. One-on-one interviews were conducted in order to obtain qualitative data, which were grouped into meaningful categories according to their themes. The findings revealed that families find ICTs useful but with limitations. Children reported that they are close to their seafarer fathers but not as much as that of children and their fathers, who are not working abroad. Moreover, they prefer Face-to-Face communication with their fathers. Finally, the mothers generally become the intermediary between the fathers and children in their communication.